WEB-BASED IMPLEMENTATION OF REPLENISHMENT PROCESS IN DISTRIBUTION CHANNELS - A CASE STUDY - Lecic-Cvetkovic, Danica; Atanasov, Nikola; Babarogic, Sladjan; Anicic, Nenad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
Demand-driven replenishment moves organizations away from a dependence on forecasts based on retrospective data and enables them to become responsive to what is actually occurring, or predicted to occur, at the distribution channels. In order to respond rapidly to demand changes, the institution of better information systems to help the channel better align inventory holding with demand is important. This case study explores working practices of procurement in distribution channels and examines the role of better demand information and retail inventory in enabling better control in retail behavior. The solution proposed in this paper is a knowledge system which provides the decision maker with better characteristics of distribution channels such as quick response, efficient inventory management, collaborative planning and forecasting.